Electronic structure of BaFeO3 studied by X‐ray spectroscopy. Issue 6 (30th March 2015) - Mizumaki, Masaichiro; Fujii, Hitoshi; Yoshii, Kenji; Hayashi, Naoaki; Saito, Takashi; Shimakawa, Yuichi; Uozumi, Takayuki; Takano, Mikio; Tsuboi, Nozomu; Wakita, Kazuki; Yamada, Akira; Shirakata, Sho; et al.
Abstract We investigated the electronic structure of BaFeO3 by using HAXPES and XAS measurements and first principle studies. The experimental and theoretical results indicated that BaFeO3 is a negative charge transfer compound. We concluded that the on‐site Coulomb energy and the strong hybridization between Fe‐3d and O‐2p orbitals play a very important role of emergence of negative charge transfer. And we found the new structure in the Fe‐2p XPS spectrum and concluded this structure is originated from non‐local screening. (© 2015 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)